(untitled) (World Bulletin of Management and Law, 2023)
This article describes the popularization of teleworking, which today is one of the atypical forms of work, as well as the regulation of this form of employment by the legislation of Uzbekistan, the new Labor Code. The concept of teleworking, working hours and rest time of teleworkers, vacation, the procedure for remuneration for their work, forms of mutual cooperation between employer and employee are covered. The article also describes the features of organizing the work of remote employees, the procedure for concluding and terminating an employment contract with them